Increased Alkaline Phosphatase Activity in the Somatic Extract of Hydatid Cyst Protoscoleces upon Treatment with Albendazole, an Implication for in vitro Evaluation of Drug Efficiency - Ali Farahnak; Leila Zaki; Mohamad Bagher Molaei Rad; Abolfazl Golestani; Mohammad Reza Eshraghiyan (Pasteur Institute of Iran, 2018)
Introduction: Hydatidosis is an endemic parasitic disease of humans in Iran, and Albendazole (ABZ) is a drug of choice for treatment of this infection. As the Alkaline phosphatase (ALP) is necessary for the metabolism of parasites, this study was aimed to evaluate the effect of ABZ on ALP enzyme activity in hydatid cyst parasite as a marker for drug efficiency. Methods: In the present study, the ALP activity level was estimated in the extracts of the untreated parasite (Hydatid cyst protoscoleces) as well as the ABZ-treated samples with a final concentration of 100 µg. The protein concentration and the protein bands in the extracted samples were analyzed by Bradford and sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) methods, respectively. Results: The results showed that the mean value of the ALP activity level of the treated samples (0.474 U/ml/mg) was significantly higher than that of untreated samples (0.205 U/ml/mg) (P<0.05). SDS-PAGE analysis demonstrated the higher intensity of the 59 kDa protein band in ABZ-treated samples, compared to the untreated sample. Conclusion: Considering the effect of the ABZ drug on ALP activity in the hydatid cyst protoscoleces, this enzyme might be regarded as an indicator for the effectivity of drug on this parasite.